Underestimated species diversity in Zhangixalus (Anura, Rhacophoridae) with a description of two cryptic species from southern China - Yuanqiang Pan; Shuo Liu; Ju Chen; Guohua Yu (Zoosystematics and Evolution)
It has been shown that species diversity of tree frogs in the genus Zhangixalus might have been underestimated. In this study, based on previously published data and newly collected samples from China, we constructed a phylogeny of the genus Zhangixalus using mitochondrial 12S rRNA-tRNAVal-16S rRNA genes and revealed two novel lineages of Zhangixalus from southern China, one containing newly collected samples from Pingbian, Yunnan, and one containing samples from Chengbu, Hunan. Combining evidence from morphological comparison and species delimitation, we described these two lineages as two new species. Zhangixalus daweishanensis sp. nov. from Mt. Dawei, Pingbian is sister to Z. dorsoviridis, and it can be distinguished from congeners by body size medium (SVL 30.0‒33.5 mm in males and 43.7‒50.7 mm in females); heels not meeting when legs positioned at right angle to body; internal vocal sac; dorsum uniformly green; black blotches in axilla, groin, and posterior part of thigh; and throat yolk yellow. Zhangixalus nanshanensis sp. nov. from Nanshan National Park, Chengbu, Hunan, which has been confused with Z. nigropunctatus, is sister to the clade of Z. lishuiensis and Z. zhoukaiyae and is distinguishable from congeners by body size medium (SVL 28.1‒36.7 mm in males and 45.2 mm in a female); dorsum uniformly green; vocal sac external; throat yellow with greyish brown blotches; outer metatarsal tubercle absent; heels not meeting when legs positioned at right angle to body; and black blotches in axilla, groin, and posterior part of thigh. In addition, we considered the samples of nominal Z. dorsoviridis from Son La, Vietnam represent a cryptic species, and more studies are required to unravel the taxonomy and distribution of Z. dorsoviridis and Z. nigropunctatus complexes, as the taxonomic status of some records of these two species in China also remains unclear. We supported that Z. duboisi and Z. omeimontis are distinct from each other and considered that Z. zhoukaiyae and Z. lishuiensis are two separate species.